Comparative Approaches to Governance and Management of Water Resources in North America - Christopher Brown (VertigO, 2010)
In the post NAFTA era, Canada, Mexico, and the United States face a range of water resource management issues. These challenges include meeting increasing demands for water while also dealing with ecosystem management issues, attempting to balance the demands of riparian states in both upstream and downstream contexts, dealing with the extraction of groundwater and the potential overdraft of shared aquifers (especially in sole source aquifer areas), and coping with persistent water quality issues. In this paper, I provide an overview of the above issues and the North American context and review the experience of different regions in North America, specifically examining the U.S.-Canada and U.S.-Mexico border region and seeking insights from one region that may be useful in the other region. As such, this is an updated version of a paper that I presented at Laval University in 2005, drawing on more recent experience.